Cholecystoduodenal Fistula related Acute Cholecystitis - Ergin, Anil; Iscan, Yalın; Fersahoglu, Mehmet Mahir; Bulut, Nuriye Esen; Ciyiltepe, Huseyin (Eastern Journal of Medical Sciences, 2019)
Cholecystenteric fistulas are abnormal formations that occur spontaneously between the gallbladder and the gastrointestinal tract. Asymptomatic cases can be diagnosed incidentally as well as during surgery in patients with acute abdomen diagnosis. We present a case of cholecystoduodenal fistula detected in a patient who underwent laparoscopic exploration with a preliminary diagnosis of gallbladder perforation. Cholecystoduodenal fistulas are difficult to diagnose preoperatively and are very rare hepatobiliary emergency surgery cases.